Plastic Buckling Paradox: An Updated Review - Shamass, Rabee (Frontiers in Built Environment, 2020)
It is widely accepted that the flow theory of plasticity significantly overestimates buckling stresses and strains and, in some cases, fails to predict buckling at all, while the deformation theory, which lacks physical rigor compared to the flow theory, predicts results that are in better agreement with experimental ones. The deformation theory is therefore recommended for use in practical applications of the buckling of shells. This paper aims to review in detail the causes behind the seeming discrepancies in the results predicted by both the flow and deformation theories of plasticity, and to propose an explanation for this so-called “plastic buckling paradox” on the basis of some recent research work in the field.